Pharmacogenomics : challenges and opportunities in therapeutic implementation - Lam, Y. W. Francis; Stuart, Scott A. (Academic Press, is an imprint of Elsevier, 2019)
Pharmacogenomics: Challenges and Opportunities in Therapeutic Implementation, Second Edition, provides comprehensive coverage of the challenges and opportunities facing the therapeutic implications of pharmacogenomics from academic, regulatory, pharmaceutical, socio-ethical and economic perspectives. While emphasis is on the limitations in moving the science into drug development and direct therapeutic applications, this book also focuses on clinical areas with successful applications and important initiatives that have the ability to further advance the discipline. New chapters cover important topics such as pharmacogenomic data technologies, clinical testing strategies, cost-effectiveness, and pharmacogenomic education and practice guidelines. The importance of ethnicity is also discussed, which highlights phar, acogenomic diversity across Latin American populations. With chapters written by interdisciplinary experts and insights into the future direction of the field, this book is an indispensable resource for academic and industry scientists, graduate students and clinicians engaged in pharmacogenomics research and therapeutic implementation.